Differential Inhibition with Antifibrinolytic Agents of Staphylokinase and Streptokinase Induced Clot Lysis - Lijnen, H Roger; Stassen, Jean-Marie; Collen, Désiré (Thrombosis and Haemostasis, 1995)
The inhibitory effects of antifibrinolytic amino acids on clot lysis induced with recombinant staphylokinase (SakSTAR) or with streptokinase (SK) were evaluated in a human plasma milieu in vitro and in a hamster pulmonary embolism model in vivo. Addition of tranexamic acid to a system composed of 60 μ1 125I-fibrin-labeled plasma clots submerged in 0.5 ml human plasma, caused dose-dependent inhibition of lysis; complete lysis in 120 min required 30 nM SakSTAR or 100 nM SK and was reduced to 50% with 0.015 mM or with 0.07 mM tranexamic acid, respectively. Aprotinin also produced dose-dependent inhibition; lysis with SakSTAR or with SK was reduced to 50% of the control value with 8 KIU/ml or with 10 KIU/ml aprotinin, respectively. Thus, in human plasma in vitro the antifibrinolytic potency of tranexamic acid was 5-fold higher towards SakSTAR than towards SK, whereas that of aprotinin was comparable towards both agents.In hamsters with pulmonary embolism given 0.063 mg/kg SakSTAR or 0.20 mg/kg SK over 30 min, the antifibrinolytic potency of tranexamic acid, administered as a single bolus injection or as a bolus injection followed by continuous infusion, was 8- to 10-fold higher towards SakSTAR than towards SK (50% reduction of clot lysis with SakSTAR at 12.5 mg/kg, as compared to 100-150 mg/kg with SK). In contrast, aprotinin was equipotent towards SakSTAR and SK (50% reduction of clot lysis with 2,000 to 2,700 KlU/kg).The higher antifibrinolytic potency of tranexamic acid (which prevents binding of plasminogen to fibrin) towards SakSTAR than towards SK is most likely related to the requirement of fibrin-bound plasminogen for efficient fibrinolysis with SakSTAR. Tranexamic acid thus may be a useful and relatively specific antidote to clot lysis with SakSTAR and, at higher concentrations, to clot lysis with SK.